1925
DOI: 10.1084/jem.42.4.465
|View full text |Cite
|
Sign up to set email alerts
|

Local Immunization of Rabbits to Cutaneous Infection With Staphylococcus Aureus

Abstract: 1. Bacterial filtrates were prepared by the methods described by Besredka, but these never developed any specific growth-inhibiting factors. 2. Such filtrates produced a strictly local immunity of the areas of the skin infiltrated but such protection was never greater than that produced with the broth from which they were prepared. This immunity was manifest within 8 hours and persisted at least 15 days. 3. Transcutaneous treatment by moist dressings soaked in either filtrate or b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1928
1928
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…It is possible that the preliminary treatment of the peritoneum by repeated injections of the filtrate called forth a non-specific response on the part of the cellular elements of the peritonetim which offer a histologic barrier to aljsorption of the reacting factors. This type of non-specific imnumity was clearly demonstrated by the work of Gay (i92()) , andMallory and Marble (1925) , on mobilization of monocytes in acute infections of serous cavities. attempted to determine whether intracranial injections of the provocative factors are capal)le of eliciting the phenomenon of local skin reactivity.…”
mentioning
confidence: 79%
“…It is possible that the preliminary treatment of the peritoneum by repeated injections of the filtrate called forth a non-specific response on the part of the cellular elements of the peritonetim which offer a histologic barrier to aljsorption of the reacting factors. This type of non-specific imnumity was clearly demonstrated by the work of Gay (i92()) , andMallory and Marble (1925) , on mobilization of monocytes in acute infections of serous cavities. attempted to determine whether intracranial injections of the provocative factors are capal)le of eliciting the phenomenon of local skin reactivity.…”
mentioning
confidence: 79%
“…Localized tissue innate immunity can also contribute to protection during recurrent infection, a notion supported by the work of Lam et al ( 43 ). Studies first performed in the 1920s reported that nonspecific local cutaneous immunity to S. aureus infection in rabbits could be induced by bacterial broth filtrates or by primary infection ( 44 , 45 ). This response lasted for at least 5 to 6 weeks and was contained to a relatively narrow area around the primary injection site ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies first performed in the 1920s reported that nonspecific local cutaneous immunity to S. aureus infection in rabbits could be induced by bacterial broth filtrates or by primary infection ( 44 , 45 ). This response lasted for at least 5 to 6 weeks and was contained to a relatively narrow area around the primary injection site ( 44 ). Protective immunity against S. aureus SSTIs was elucidated further in a mouse model of recurrent infection by Chan et al ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…A similar, larger sheet was Superimposed and fixed in the same way, and a ninny-tailed binder was put over all. The broth, made up according to Mallory and Marble's formula (6), contained Lieblg's beef extract and had been sterifized in the autoclave. Some leakage of it occurred along the lower edge of the dressings, and, to make up for this, 15 to 20 cc.…”
Section: Preparation Of the Skin With Broth Compressesmentioning
confidence: 99%